2020
DOI: 10.20473/jn.v15i1.17793
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acceptance and Commitment Therapy (ACT) on Depression in TB-HIV Co-infection Patients

Abstract: Introduction: The most common psychological problem in TB-HIV coinfection patients is depression. Acceptance and Commitment Therapy (ACT) is an intervention that encourages participants to change their relationships with their thoughts and physical sensations through mechanisms of acceptance and value-based action. This present study has been carried out to investigate the effectiveness of ACT in treating TB-HIV coinfection patients.Methods: This research was a quasi-experiment. This study involved 62 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This suggests that ACT has caused significant changes in the depression rates of HIV-positive people. Similar results have been reported in previous studies, showing that ACT can reduce depression among HIV patients (27).…”
Section: Diffrences Of Depression Before and After Being Given Actsupporting
confidence: 92%
“…This suggests that ACT has caused significant changes in the depression rates of HIV-positive people. Similar results have been reported in previous studies, showing that ACT can reduce depression among HIV patients (27).…”
Section: Diffrences Of Depression Before and After Being Given Actsupporting
confidence: 92%
“…A study conducted by Maria et al (2020) used TB-HIV patients as their respondents and found that ACT significantly reduces depression in the experimental group rather than in the control group where ACT was not implemented. They also explained that when the depressive person is willing…”
Section: Nursing Practices 90mentioning
confidence: 99%